Current Conditions and Problems of Digital Cultural Heritage Archive in Thailand - Chirakitnimit, Nadthanon; Laoakka, Sastra (Community and Social Development Journal, 2020)
The objective of this study is to study the current conditions and problems of the digital cultural heritage archive in Thailand by collecting data from 48 websites related to cultural heritage, 28 Thai websites and 20 foreign websites, by interviewing 8 experts and digital archive experts. Data is analyzed by recommended features in accordance with the government website standard and compared with the foreign website, and analyze interview content. The result found that, digital cultural heritage archive in Thailand still lacks features that should be standardized in various aspects such as web analytic the most lacking features, followed by display feature, supporting tools, personalized e-service and the search engine. When comparing with the foreign website it is found that digital cultural heritage archive of Thailand lacks more features that should be included such as language, data sharing, animation, navigation system, formatting, recommendations, menu using, disclaimers, policy announcements. The important issue of the digital archive is lack of preparedness and supporting factors such as aim, scope and clarity of development, data planning for management, skills and knowledge of personnel, expense or budget system administration, systematic data management, government promotion policy, equipment and technology and network cooperation.